Bridging the gap: How job satisfaction transforms career development into work-life balance—evidence from Indonesia’s emerging workforce - Shafariah, Hanuna; Gofur, Abdul (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the mediating role of job satisfaction in the relationship between career development and work-life balance (WLB) among employees in Indonesia’s emerging workforce. Grounded in Greenhaus and Allen’s (2011) Work-Family Balance model, the research challenges traditional spillover perspectives by proposing that career development enhances WLB indirectly through increased job satisfaction. Data were collected from 103 working professionals and analyzed using mediation analysis with bootstrapping techniques. The results confirm that career development significantly improves job satisfaction, which in turn positively influences WLB. The indirect effect of career development on WLB through job satisfaction was also significant, highlighting the importance of psychological fulfillment in bridging professional growth and personal well-being. These findings offer practical insights for organizations aiming to design career development programs that foster both employee satisfaction and work-life harmony. The study contributes to the literature by validating the Work-Family Balance model in a non-Western context and emphasizing the need for holistic HR policies that address both professional and personal domains.